Răspuns :
a)
[tex]a)2x + 3y - 5x + y = - 3x + 4y [/tex]
[tex]2x - 5x = - 3x[/tex]
[tex]3y + y = 4y[/tex]
[tex] = [/tex]
[tex] - 3x + 4y[/tex]
c)
[tex](2x + 3) \times (x - 1) = {2x}^{2} + x - 3[/tex]
[tex]2x \times x = {2x}^{2} [/tex]
[tex] - 2x + 3x = x[/tex]
[tex] = [/tex]
[tex] {2x}^{2} + x - 3[/tex]
[tex]a)2x + 3y - 5x + y = - 3x + 4y [/tex]
[tex]2x - 5x = - 3x[/tex]
[tex]3y + y = 4y[/tex]
[tex] = [/tex]
[tex] - 3x + 4y[/tex]
c)
[tex](2x + 3) \times (x - 1) = {2x}^{2} + x - 3[/tex]
[tex]2x \times x = {2x}^{2} [/tex]
[tex] - 2x + 3x = x[/tex]
[tex] = [/tex]
[tex] {2x}^{2} + x - 3[/tex]